2014
DOI: 10.1088/0963-0252/23/6/064002
|View full text |Cite
|
Sign up to set email alerts
|

Microplasmas ignited and sustained by microwaves

Abstract: The challenges and benefits of microwave-induced microdischarges are reviewed. Transmission lines, resonators and surface wave launchers may be used for coupling microwave power to very small plasmas. Fortunately, microplasmas are typically much smaller than the wavelength of microwaves, and the electromagnetic problem may be treated electrostatically within the plasma. It is possible to trap electrons within small discharge gaps if the amplitude of electron oscillation is smaller than the plasma size. Typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 75 publications
1
65
0
4
Order By: Relevance
“…Recently the method was applied to a MW plasma jet working in Ar and it was found that in the core of the jet the electron density is about 10 16 cm −3 [35]. …”
Section: Eamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the method was applied to a MW plasma jet working in Ar and it was found that in the core of the jet the electron density is about 10 16 cm −3 [35]. …”
Section: Eamentioning
confidence: 99%
“…The plasma density was found to be in the order of 10 13 cm −3 which is in good agreement with other methods. MW scattering can be applied to plasmas of low ionization degree with a minimum n e of approximately 10 9 cm −3 and shows possibilities of obtaining the decaying plasma parameters and information about loss rates of electrons [41,44]. It has to be noted here that a drawback of the method is that only volume averaged value of n e can be measured.…”
Section: Microwave Radiation Scatteringmentioning
confidence: 99%
“…The plasma was generated by applying microwave power to a transmission line terminated in a small discharge gap. This type of source was compared to other microwave source designs in a review paper; 13 the characteristics of the present design are outlined in Sec. II A.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Thus, the present design adds a new class of generators to the existing plasma generator flora, which are discussed in several reviews. [14][15][16][17][18][19] Unlike all previous plasma generators, the all-dielectric design of our generator makes it ideal for interactions with high-frequency electromagnetic waves.…”
mentioning
confidence: 99%